Effectiveness of Total Physical Response - Singh, Jai Prakash (Academic Voices: A Multidisciplinary Journal, 2011)
The present article is an attempt to overview Total Physical Response as a method of language teaching and to show its implications in English language classroom, particularly in vocabulary teaching at elementary grades. Keywords Total Physical Response(TPR), lesson plan, intervention, target language, word association DOI: http://dx.doi.org/10.3126/av.v1i0.5303 Academic Voices 2011; 1: 20-22